Influência do preparo do esmalte no manchamento marginal de laminados cerâmicos - Zago, Renata Ragagnin (2014)
The aim of this study was to evaluate the marginal staining of ceramic laminates cemented with and without the presence of enamel preparation. Thirty-two (32) permanent central incisors were selected and randomly divided into two groups (CP and SP). In group-CP (n = 16) the laminates were bonded to the prepared enamel and in group-SP (n=16) laminates were cemented directly over the intact enamel, with no preparation. The preparation and cementation were standardized and performed by a single operator. Each group was subdivided into two subgroups (n = 8) which correspond to different immersion media - coffee and water ( SPc , SPa , CPc and CPa ). After an immersion period of 10 days, stereomicroscope pictures with 20X of the mesial, distal, cervical and incisal surface of each specimen were made. The interfaces tooth - resin cement - laminate were evaluated by three blind, trained and calibrated examiners. Data were subjected to statistical Kruskal - Wallis and Mann - Whitney analysis. The prepared group as well as the unprepared group showed higher marginal staining when immersed in coffee. When immersed in coffee, the prepared laminates presented more marginal staining then unprepared laminates. But when immersed in water there was no statistically significant difference between the groups. The adhesive interface of ceramic laminates cemented on prepared enamel presented more marginal staining than laminates cemented on intact enamel, with no preparation, after immersion in staining solution.